1984
DOI: 10.1210/endo-115-2-605
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Superfusion of Rat Anterior Pituitary Cells: Effects of Repeated Pulses of Gonadotropin-Releasing Hormone at Different Doses, Durations, and Frequencies*

Abstract: We investigated the temporal release of LH by rat pituitary cells superfused with repeated pulses of GnRH at different doses (amplitudes), frequencies, and pulse durations. Anterior pituitary (AP) cells prepared from ovariectomized rats were cultured on bio-beads and then placed in columns and superfused. The cells were stimulated intermittently for 24 h with synthetic GnRH given as pulses of 6-, 10-, or 15-min duration at frequencies of one pulse per 30, 60, or 90 min. In the first experiment we tested the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
9
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 33 publications
4
9
0
Order By: Relevance
“…The present results clearly demonstrated that these changes in LH secretion were due to an increase in the fre quency of LHRH pulses released into the pituitary portal circu lation. Consistently, it has been reported in both in vivo and in vitro studies that an increase in the frequency of the pulsatile administration of LHRH resulted in an increase in the mean LH concentration and a decrease in the amount of LH secreted in response to each LHRH pulse [21][22][23].…”
Section: Discussionsupporting
confidence: 82%
“…The present results clearly demonstrated that these changes in LH secretion were due to an increase in the fre quency of LHRH pulses released into the pituitary portal circu lation. Consistently, it has been reported in both in vivo and in vitro studies that an increase in the frequency of the pulsatile administration of LHRH resulted in an increase in the mean LH concentration and a decrease in the amount of LH secreted in response to each LHRH pulse [21][22][23].…”
Section: Discussionsupporting
confidence: 82%
“…The LH release in response to 0.5 and 2.5 ng GnRH was not influenced by thyroid ectomy and reflected a desensitization of a releasable pool of LH in Tx rat AP to higher doses of GnRH ranging between 0.5 and 2.5 ng, as described by Liu and Jackson [ 17] in the study of LH release by rat AP cells superfused with repeated pulses of GnRH at different doses. They found that rat AP cells subjected to pulsatile administration of low doses of GnRH (e.g.…”
Section: Discussionsupporting
confidence: 56%
“…(i) There is a linear relation between the quantity of LH released by gonadotropes, either in vitro (10,11) or in vivo (12,13), and the quantity of GnRH administered acutely. The concentrations of GnRH achieved in these studies fell within the range measured in pituitary portal blood of ovariectomized monkeys (14)(15)(16), humans (16), ovariectomized ewes (17), and rats (18) or in the extracellular fluid of the medial basal hypothalamus of rats (19) and sheep (20) sampled by "push-pull" perfusion.…”
Section: Discussionmentioning
confidence: 99%